MEMBEDAH MAKNA JIHAD DALAM AL-QURAN MELALUI LENSA AMIN AL-KHULI: PERSPEKTIF PSIKOLOGIS - Iklil Faza; Silvia Ifta Fauziyah (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: This article discusses the meaning of jihad in the Qur'an through Amin Al-Khouli's perspective with a psychological approach, which reveals the physical and non-physical dimensions of jihad as a holistic struggle. In the physical context, jihad at the time of the Prophet Muhammad served as a response to existential threats to Muslims, in which the Qur'an provided psychological encouragement to build courage and solidarity. Meanwhile, non-physical jihad, such as jihad against lust, became a form of spiritual struggle to control ego and worldly urges, referred to as jihad akbar. Al-Khouli's interpretation emphasizes the importance of understanding jihad broadly as a moral, intellectual and social struggle, which is relevant to correcting misunderstandings, including the issue of Islamophobia, and strengthening the meaning of jihad as a collective effort for the good of the ummah. Keyword: Jihad, psychology, relevant.                                                                                                           Abstrak: Artikel ini membahas makna jihad dalam Al-Qur'an melalui perspektif Amin Al-Khouli dengan pendekatan psikologi, yang mengungkap dimensi fisik dan non-fisik jihad sebagai perjuangan holistik. Dalam konteks fisik, jihad pada masa Nabi Muhammad SAW berfungsi sebagai respons terhadap ancaman eksistensial umat Muslim, di mana Al-Qur'an memberikan dorongan psikologis untuk membangun keberanian dan solidaritas. Sementara itu, jihad non-fisik, seperti jihad melawan hawa nafsu, menjadi bentuk perjuangan spiritual untuk mengendalikan ego dan dorongan duniawi, yang disebut sebagai jihad akbar. Penafsiran Al-Khouli menekankan pentingnya memahami jihad secara luas sebagai perjuangan moral, intelektual, dan sosial, yang relevan untuk meluruskan kesalahpahaman, termasuk isu Islamofobia, dan memperkuat pemaknaan jihad sebagai upaya kolektif untuk kebaikan umat. Kata kunci: Jihad;psikologi;relevan.